Development of Integrated QR Code Module on Physics Learning Module to Increase Learning Interest and Knowing Students' Digital Literacy - Firdha Kusuma Ayu Anggraeni; Sri Handono Budi Prastowo; Trapsilo Prihandono (Jurnal Penelitian Pendidikan IPA, 2022)
A solution for learning in the form of a module integrated with a QR code is offered to assist lecturers in delivering material to students of Physics Education Study Program. With the integrated QR code physics learning module, it is able to increase interest improve students' digital literacy. The method of research is research and development and the analysis was carried out based on the questionnaire data processing. The result shows that the increase of average percentage value of the measurement of interest in learning is 22.24% and the average percentage value of the measurement of digital literacy ability is 80.90%. Based on the results, the conclusions are the integrated QR code on physics learning module is effective to increase interest in learning and students have high digital literacy skills because they are able to take advantage of digital media for the learning process